Long-term Outcomes of Parathyroidectomy in Kidney Transplant Recipients with Persistent Hyperparathyroidism - Po-Yu Tseng; Wu-Chang Yang; Chih-Yu Yang; Der-Cherng Tarng (Karger Publishers, 2015)
Background/Aims: Hyperparathyroidism (HPT) is a common complication of chronic kidney disease and contributes to hypertension and cardiovascular risks. Successful kidney transplantation corrects abnormal mineral metabolism, but persistent HPT is still observed in up to 25% of patients one year after transplantation despite renal function improvement. The purpose of this study was to examine the long-term effects of parathyroidectomy (PTX) on blood pressure (BP) and graft function in patients with persistent post-transplant HPT. Methods: This is a retrospective study of renal allograft recipients at a single institute. Records from all the patients who received kidney transplantation at the Taipei Veterans General Hospital between 2004 and 2012 were reviewed and enrolled 19 patients who underwent PTX for persistent post-transplant HPT. Preoperative and postoperative clinical and biochemical data were compared. Matched controls (n = 19) in the corresponding time span were enrolled for graft function comparisons. Results: The mean systolic BP (127.7 ± 14.3 to 119.5 ± 12.7 mmHg, p = 0.028, 1 year after PTX; 127.7 ± 14.3 to 117 ± 12.4 mmHg, p = 0.007, 2 years after PTX) and pulse pressure (PP) (51.3 ± 10.7 to 44.3 ± 11.6, p = 0.019 1 year after PTX; 51.3 ± 10.7 to 44.9 ± 12.5 mmHg, p = 0.028, 2 years after PTX) reduced significantly at 1 year and 2 years of follow-up. However, no significant change of diastolic BP was observed. The improvement of SBP, DBP and PP was not correlated with the reduction of serum calcium level 1 year after PTX. The estimated glomerular filtration rate decreased significantly from 74.0 ± 20.5 mL/min/1.73m2 preoperatively to 68.2 ± 24.8 mL/min/1.73 m2 12 months after PTX but recovered at 15 months and lasted to 2 years after PTX. The all-cause hospitalization rate 1 year after PTX tended to be higher than that 1 year before PTX (105.3 versus 47.4 per 100 patient-years; RR, 2.22; 95 % CI: 0.97-5.54), but there was no significant difference between them. Conclusions: Our study demonstrated systolic BP and PP reduced 2 years after PTX and there was no significant difference between the peri-operative all-cause hospitalization rates. In addition, kidney allograft function impaired temporarily 12 months after PTX, but recovered 15 months after PTX.